Efficacy of acupuncture combined with mirror therapy in the treatment of post-stroke limb movement disorders: a systematic review and meta-analysis of randomised controlled trials - Ke, Weihao; Cheng, Hongxin; Ren, Xiaoxuan; Yang, Liang; Lai, Xiaomin; Wang, Zhenyu (Frontiers in Rehabilitation Sciences, 2024)
ObjectiveTo investigate whether the combination of acupuncture and mirror therapy can improve motor impairment in stroke patients.DesignA systematic review and meta-analysis of randomised controlled trials.Data sourcesCNKI, Wanfang, PubMed, Embase, Vip, web of since, Cochrane database and CBM database.Eligibility criteria for selecting studiesThe included randomized controlled trials compared the efficacy of acupuncture therapy (AT) combined with mirror therapy (MT) against AT, MT, and conventional rehabilitation therapy on limb motor impairment in stroke patients, with independent data extraction and study quality assessment conducted. A META analysis using fixed-effect and random-effect models was performed to calculate the mean difference (MD) in motor scores and the Total effective rate RR (Risk ratio) between the AT combined with MT group and the control group.Main outcome measuresThe Fugl-Meyer Assessment (FMA) for motor function includes the FMA-T (total FMA), FMA-UE (upper extremity FMA), and FMA-L (lower extremity FMA).ResultsA total of 42 randomized controlled trials were included, involving 3,340 patients with post-stroke motor impairment. AT combined with MT was more favorable for FMA-UE (mean difference [MD] = 6.67, 95% CI [5.60–7.93], Z = 11.42, P < 0.0001), FMA-L [MD = 3.37, 95% CI (2.99–3.76), Z = 17.31, P < 0.001], and FMA-T [MD = 6.84, 95% CI (5.92–7.77), Z = 14.48, P < 0.001]. The combined AT and MT treatment was more favorable for the Modified Barthel Index (MBI) score in post-stroke motor impairment [MD = 10.82, 95% CI (8.52–13.12), Z = 9.22, P < 0.001]. AT combined with MT was more favorable for the Modified Ashworth Scale (MAS) [MD = −0.34, 95% CI (−0.66 to −0.03), Z = 14.48, P < 0.001]. AT combined with MT was more favorable for the Total effective rate in treating post-stroke motor impairment (relative risk = 1.27, 95% confidence interval [CI] [1.19–1.37], Z = 6.54, P < 0.001).ConclusionsAT combined with MT can effectively improve patients’ motor function and daily living abilities.Systematic Review RegistrationPROSPERO, identifier, CRD42024559992.